African Economic Development Evidence, Theory, Policy - Cramer, Christopher (Oxford University Press, 2020)
This book challenges conventional wisdoms both about economic performance and about policies for economic development in African countries. Its starting point is the striking variation in economic performance: unevenness and inequalities form a central fact. The authors highlight not only differences between African countries but also variations within countries, differences often organized around distinctions of gender, class, and ethnic identity. For example, school dropout and neonatal mortality have been reduced, particularly for some classes of women in some areas. Horticultural and agribusiness exports have grown far more rapidly in some countries than others. These variations (and many others) point to opportunities for changing performance, reducing inequalities, learning from other African policy experiences, and escaping the ties of structure and legacies of a colonial past. The book rejects teleological illusions and Eurocentric prejudice, but does pay close attention to the results of policy in more industrialized parts of the world. Seeing the contradictions of capitalism for what they are-fundamental and enduring-may help policy officials protect themselves against the misleading idea that development is likely to be a smooth, linear process, or that it would be were certain impediments removed. The authors criticize a wide range of orthodox and heterodox economists, especially for their cavalier attitude to statistical sources. Drawing on decades of research and policy experience, they combine careful use of available evidence from a range of African countries with heterodox political economy insights (mainly derived from Kalecki, Kaldor, and Hirschman) to make the policy case for specific types of public sector investment.